Strain pattern and T-wave alterations are predictors of mortality and poor neurologic outcome following stroke - Braga, Gabriel P. [UNESP]; Gonçalves, Renato S. [UNESP]; Minicucci, Marcos F. [UNESP]; Bazan, Rodrigo [UNESP]; Zornoff, Leonardo A. M. [UNESP] (Wiley, 2020)
Background: Stroke is associated with electrocardiogram (ECG) abnormalities. However, the role of strain pattern as predictor of poor neurologic outcome and mortality after stroke has not yet been demonstrated. Hypothesis: ECG abnormalities, with a particular focus on ST-segment changes, are predictors of mortality and neurologic disability 90 days after stroke. Methods: Patients with up to 24 hours of stroke were prospectively recruited. An ECG was taken at the time of admission. The patients' clinical evolution was evaluated during hospitalization and after discharge by means of a prescheduled return in 90 days. The degree of disability was measured by the modified Rankin scale (mRs). In relation to the mRs, patients were divided into those with scores from 0 to 2 and those with scores equal to or greater than 3 at the end of the observation period. Results: Of the 112 patients studied, 29 (25.8%) died during the study period. Patients who died presented higher National Institute of Health Stroke Scale and mRs scores on admission, elevated biomarkers of myocardial necrosis, and abnormalities on the ECG. The prevalence of ECG abnormalities was 63%. A logistic regression model showed that strain pattern and T-wave alterations were predictors of mortality (odds ratio [OR]: 12.970, 95% confidence interval [CI]: 1.519-110.723, P =.019; OR: 3.873, 95% CI: 1.135-13.215, P =.031, respectively) and mRs at 90 days (OR: 12.557, 95% CI: 1.671-94.374, P =.014; OR: 15.970, 95% CI: 3.671-69.479, P <.001, respectively) after stroke, adjusted by sex, age, stroke subtype, entrance NIH, previous mRs score, and stroke thrombolysis. Conclusion: Strain pattern and T-wave alterations were predictors of mortality and poor neurologic outcome 90 days after stroke.
Keywords: electrocardiogram; mortality; neurologic disability; outcomes; prediction; stroke